Frequency analysis of donor-reactive cytotoxic T lymphocyte precursors in liver allograft recipientsMarcia Liane Lobo Eberspächer, Gerd Otto, Christian Herfarth, Dieter Kabelitz - Eberspächer, Márcia Liane Lôbo; Otto, Gerd; Herfarth, Christian; Kabelitz, Dietrich (Transplantation, 1994)
The frequency of donor-reactive and of third partyreactive cytotoxic T lymphocyte precursors (CTLp) was determined by limiting dilution analysis in the peripheral blood of 13 liver allograft recipients before (pre-tpx) and at various intervals (4 to 22 months) after (post-tpx) transplantation. In 6 of 13 patients with stable graft function, no change of donor-reactive CTLp occurred within 9 to 17 months post-tpx, and high levels of donor-reactive CTLp (frequencies ranging from 1/1024 to 1/13,295) were maintained. In contrast, a 4-11-fold reduction of donorreactive CTLp frequencies was observed in 5 patients within 4 to 22 months post-tpx; in 3 of these patients the measured frequency of donor-specific CTLp dropped to biologically irrelevant levels (1/43,800 to 1/150,000). However, a 5-7-fold increase of the post-tpx frequency of donor-reactive CTLp was observed in two additional patients with stable graft function. Taken together, these results demonstrate that the frequency analysis of donorreactive CTLp in the peripheral blood does not closely correlate with the clinical outcome. Thus, stable liver allograft function after >1 year of transplantation can be associated with a specific deletion, unaltered levels, or even an increase in the frequency of circulating donor-reactive CTLp.